Analysis of the quality of service of PT Bheta Yard Nusantara towards customer satisfaction as a contracting company in the field of services and procurement of goods - Nugraha, Augit Izza; Wulandari, Astri (Edelweiss Applied Science and Technology, 2025)
PT Bheta Yard Nusantara is a contractor company focused on providing services and procuring goods across various industrial sectors. This study aims to analyze the quality of service provided by the company and its impact on customer satisfaction. The research design employs a quantitative approach using the Importance-Performance Analysis (IPA) method to evaluate customer perceptions and expectations. Primary data were collected through questionnaires distributed to customers who have utilized the company’s services. The findings indicate that the total average service performance reached 3.22, while customer expectations stood at 3.18, demonstrating that the company’s performance aligns with customer expectations. The implications of this research emphasize the importance of improving service quality in areas deemed significant by customers to enhance satisfaction and loyalty. The conclusion of the study is that while the company has shown adequate performance, there remains room for improvement, particularly in responsiveness and information transparency. Practical implications suggest that the company should implement service enhancement strategies focused on customer needs to maintain competitiveness in an increasingly tight market.